Technology transfer strategy for women in coffee livestock integration as climate-smart agriculture practice - Wulandari Suci (EDP Sciences, 2021)
The Integrated Crop Livestock Systems (ICLS) is considered an important strategy to cope with climate change issues in coffee plantations. However, the involvement of women in the coffee livestock integration system is still limited. This condition is related to women’s limited knowledge and technical capacity because there is no technology transfer model based on the requirements and needs of women. The purpose of this paper is to identify problems related to women’s participation and formulate technology transfer strategies to increase women’s participation in coffee livestock integration as a Climate-Smart Agriculture (CSA) practice. The research was conducted in Bandung Regency, West Java, as Indonesia’s Arabica coffee development center. Data analysis was performed using descriptive statistics and Interpretive Structural Modeling (ISM). The role of women in management and decision-making in the development of coffee livestock is relatively low. Their involvement is still complementary, lacking initiative and limited participation due to internal and external issues. The strategies are related to three main areas: knowledge development, skill development, and technology utilization. The program derived from the strategies is expected to develop women’s capacity both individually and in groups.